Growth response of pakcoy (Brassica rapa L.) due to difference dosage and time of giving bokashi - I Wayan Merta; Ahmad Raksun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Pakcoy is one of the commodities favored by the people of Indonesia. The presence of nutrients aroundÃÂ the plant root system greatly affects the growth of pakcoy. The availability of nutrients can be increased by fertilizing. Fertilization of plants can be done by using bokashi. Study on the growth response of pakcoy due to differences in dosage and time of giving bokashi was conducted to determine: (1) the growth response of pakcoy due to bokashi treatment,ÃÂ (2) the growth response of pakcoy due to difference in the time of giving bokashi, (3) the growth response of pakcoy due to the interaction between the dose and the time of giving bokashi. Completely randomized design with 3 replications was used in the study. The growth pakcoy parameters were plant height, number of leaves and leaf length. The result showed that: (1) plant height, number of leaves and leaf length had a positive response to bokashi treatment with the best bokashi dose is 15 tons per hectare, (2)ÃÂ plant height, number of leaves and leaf length of pakcoy responded to the time of giving bokashi, the highest growth parameters were pound in pakcoy given bokashi 30 days before planting. (3) plant height, number of leaves and leaf length were not significantly different due to the interaction between dose and time giving bokashi